Molecular techniques and stable isotope ratios at natural abundance give complementary inferences about N2O production pathways in an agricultural soil following a rainfall event. (September 2015) - Snider, David; Thompson, Karen; Wagner-Riddle, Claudia; Spoelstra, John; Dunfield, Kari
Abstract: The abatement of anthropogenic nitrous oxide (N2 O) emissions depends on sound management of manure nitrogen (N) and an ability to track and predict manure-derived microbial N2 O production in soils. The objective of this study was to investigate the utility of applying a novel combination of micrometeorological, stable isotope, and molecular methods to determine the short-term dynamics of N2 O production processes in soil. Nitrous oxide emissions were continuously monitored in two drought-stressed agricultural fields treated with liquid dairy manure applied either in the fall or spring over an N2 O emission event triggered by a heavy rainfall. In situ δ 15 N–N2 O and δ 18 O–N2 O measurements were used in conjunction with abundance (DNA) and potential activity (cDNA) measurements of key microbial N cycling gene and transcript (mRNA) targets to evaluate if these two techniques provided similar inferences about N2 O soil processes occurring over the emission event. Soil gas was sampled at 4 depths along a profile from 10 to 50 cm below the surface and a multi-layer diffusion model was used to calculate the vertical N2 O fluxes, the change in storage, and the net production of N2 O in each layer. The rainfall event triggered N2 O production in both fields at all depths, but the uppermost soil layer was the main source of N2 O emissions throughout. Soil concentrations and surface emissions of N2 O increased rapidly reaching a maximum 4 d following rainfall and were accompanied by a significant increase in the abundance of both nitrifier and denitrifier genes and total bacterial and archaeal genes and transcripts. A similar increase in the transcription of functional genes was not detected, but relatively high levels of archaeal ammonia monooxygenase ( crenamoA ) and bacterial nitrite reductase ( nirS ) transcripts were present in both fields throughout the study, indicating nitrification and denitrification were occurring concomitantly. High levels of H2 O–NOx oxygen exchange at our study site precluded the use of δ 18 O–N2 O values to separate different sources. Prior to the rain, both fields had very small amounts of soil ammonium and the stable nitrogen isotope characterization of N2 O in the dry soil implicated denitrification as the main source of N2 O rather than nitrifier-denitrification or hydroxylamine oxidation. Following the rain event, the δ 15 N–N2 O values showed a change in production process as nitrifier-denitrification became a more dominant N2 O source. By pairing stable isotope measurements with molecular analyses we were able to verify that these two approaches provide similar inferences about soil N2 O production processes during an emission event in manure-applied fields. Although significantly higher N2 O flux and N2 O accumulation in the soil profile were observed for the field receiving manure in the spring, differences in isotope signal and molecular analysis between fields were not observed. To our knowledge this is the first time that isotope and molecular techniques have been used to study processes resulting in N2 O production in manure-amended soils in situ . Whereas stable isotopes were useful for directly tracking the pathways of N2 O production, molecular analyses revealed the status of the N cycling communities before, during and after the emission event. This information helped explain the observed differences in emissions between fields, and it helped to support our isotope-based conclusions. Highlights: Rain-induced soil N2 O production was quantified using micrometeorological methods. N2 O production processes were studied using both molecular and isotopic tools. Before the rain, the small baseline N2 O flux was produced by denitrification. After the rain, nitrifier-denitrification and denitrification were key sources. Isotope and molecular approaches provided similar inferences about N2 O processes.